PENGARUH LIKUIDITAS, PROFITABILITAS, SOLVABILITAS, DAN UKURAN PERUSAHAAN TERHADAP HARGA SAHAM PERUSAHAAN FARMASI DI BEI - SYAIFUL S, ACHMAD Syaiful (Jurnal Akuntansi AKUNESA, 2012)
The aim of this research to determine the effect of the solvency (DER), liquidity (CR), profitability (ROA), and firm size either simultaneously or partially on the stock prices in the pharmaceutical industry sector. Method used in this research is descriptive verification. The analytical method used is multiple linear regression analysis. The results indicate that the ROA, DER, and CR partially have not significant effect on stock prices. Firm size partially has significant effect on stock prices. The ROA, DER, CR, and total assets simultaneously have significant effect on stock prices.Keywords : solvency, liquidity, profitability, firm size, stock prices